a semiotic analysis of trigonometry in the didactic book of mathematics - Miranda, Jessica; Fontes, Maurício; Martini, Luiz; Miranda, Felipe (Revista Hipótese, 2019)
Trigonometry Teaching is an integral part of Mathematical knowledge and as such has many applications within mathematics (Calculus, Analytical Geometry, etc.) as well as outside it, such as (Uniform Retilinear Movement - in Physics, etc., ). The aim of the present work is to analyze descriptively the eighty trigonometry activities in a textbook of the first year of high school, taking into account the theory of registration of semiotic representations, and to verify the type of problems that characterize them (open or closed), the type of treatment predominant (algebraic, graphical or numerical), connections with other areas of education and finally the conversions and treatments present in each question. The sample was intentional in that we analyzed all the questions that involve trigonometry in the book of the first year of the High School recommended by PNLD. The Methodology used was qualitative with a descriptive study. The results show a predominance of closed problems and the conversion of the symbolic language to the algebraic one.
Keywords: Semiotics; Textbook; Trigonometry; PNLD